Academic cheating in the context of a pandemic: report of physiotherapy students - Reinoso González, Eduardo (Spanish Journal of Medical Education, 2022)
Introduction: Within the framework of the current health scenario, medical educationhas had to align its training processes based on confinement and the e-learning modality. SARSCOV-2 prompted the massive use of technology to continue with the different programs, whichhas not only meant a change in the modality of content delivery, clinical practices and evaluation,but also a significant increase in academic cheating behaviors by the student body. Objective: Todescribe the report of second-year health students on academic cheating in the context of apandemic. Method: Qualitative hermeneutic phenomenological study with content analysistechnique, through data collection by individual interview to a sample of 73 second-yearphysiotherapy students at the Universidad Católica de la Santísima Concepción, Chile. Results:Categories of student discourse on academic cheating were obtained: a) Motivation of thephenomenon, b) Recommendations to avoid the phenomenon, c) Obstacles to the phenomenon, d)Facilitators of the phenomenon and e) Reflections on the phenomenon. Conclusions: Students whoadmit to cheating academically during the e-learning modality relate the virtual modality as oneof the facilitators of this behavior, which strengthens social and academic ties with their peers andrecommends modifications in the forms of evaluation.